Effects of Pueraria extracts on growth performance, immune function, and immune-related gene expression of Wuzhishan piglets - Wu, Hongzhi; Peng, Weiqi; Yu, Xilong; Zhang, Xiaoyu; Ji, Fengjie; Shen, Qian; Lv, Renlong (Frontiers in Veterinary Science, 2025)
Pueraria extracts contain phytoestrogens, particularly isoflavones such as daidzein and genistein, which have been used in traditional Chinese medicine for centuries due to their various health benefits. Wuzhishan pig is a small pig unique to China, native to Wuzhishan, Hainan Province. Pueraria extracts have been widely utilized in the production of various animals. However, there are relatively few reports regarding their application in piglets, particularly in local pig breeds. The experiment aimed to investigate the effects of dietary Pueraria extracts on the growth performance, immune function, and immune-related gene expression of Wuzhishan piglets. Forty-eight piglets were randomly divided into four groups, each with six replicates and two piglets in each replicate. The control group (CON) was fed the basal diet, and the other groups were given 400, 600, and 800 mg/kg Pueraria extracts (PE1, PE2, and PE3, respectively). Compared with the CON, (1) the dietary Pueraria extracts increased the average daily gain and decreased the feed conversion ratio in PE2 and PE3 (p < 0.05); (2) the dietary Pueraria extracts increased the serum immunoglobulin M and complement 3 and 4 contents in PE2 (p < 0.05); (3) the serum ALB and ALP contents in groups treated with the Pueraria extracts were higher (p < 0.05); (4) the ALT and GOT contents were lower (p < 0.05) in groups treated with Pueraria extracts; (5) the dietary Pueraria extracts increased the Bacillus acidi lactici and Saccharomycetes contents, and decreased the Escherichia coli and Salmonella contents in the jejunum in PE1, PE2, and PE3 (p < 0.05); (4) the dietary Pueraria extracts ameliorated the relative expression of Interleukin-10, Tumor necrosis factor-α, Mucoprotein 2, Transforming growth factor-β1, Zonula occludens-1 in jejunum mucosa (p < 0.05). In this study, adding 600 mg/kg dietary Pueraria extracts to the Wuzhishan piglets’ diets improved the growth performance, immune function, and immune-related gene expression. This study laid a theoretical foundation for popularizing and applying Pueraria extracts in local pig production.